Impact of rare-earth ions incorporation in high mobility wide bandgap degenerated semiconductors: study considering many-body effects and advanced optical dispersion models - (:unkn) unknown (My University, 2026)
The aim of this research project proposal is to study the optoelectronic and electrical properties of IZO, IGZO and IZrO thin films and assess the impact of rare-earth (RE) incorporation in their structure. We plan on using recently developed advanced opt